By The Ore Docks : A Working People's History Of Duluth - Hudelson, Richard (Book collections on Project MUSE., 2006)
Located on the shore of Lake Superior near the Iron Range of Minnesota and, for much of its history, the site of vast steel, lumber, and shipping industries, Duluth has been home to people who worked tirelessly in the rail yards, grain elevators, and harbor. Here, for the first time, By the Ore Docks presents a compelling, full-length history of the people who built this port city and struggled for both the growth of the city and the rights of their fellow workers. In By the Ore Docks, Richard Hudelson and Carl Ross trace seventy years in the lives of Duluths multi-ethnic working classScandi.